The individual differentiated training design of health-promoting shaping with mature age women - Kostyuchenko, V.F.; Skidan, A.A.; Vrublevskiy, E.P. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2018)
Purpose: theoretical justification, development, and approbation of individual differentiated training design of health-promoting shaping with mature age women. Material: women aged from 21-55 years (n=86) participated in the research. It was determined the initial level of their morphofunctional state and physical fitness (it was considered phases of an individual ovarian menstrual cycle). It was revealed criteria of the individual differentiated approach to the design of health-promoting shaping training (it was considered biorhythms of the female body). It was realized the nine-months macrocycle of health-promoting shaping training. The macrocycle consisted of three stages. Two programs - power and aerobic orientation are developed for training at the main stage of a macrocycle. Distribution of loads, their duration, intensity, and volume was regulated individually. It was considered the hormonal background of a female body during an ovarian menstrual cycle. Results: It is observed an increase in the level of a morphofunctional state and physical fitness of women. It is revealed statistically reliable changes of all physical development indicators, a functional state and physical fitness of women. Conclusions: The individual differentiated approach to training design of improving shaping allows to operate a morphofunctional condition of women organism more purposefully. Such an approach promotes organism adaptation to training loads. It also promotes an increase in the level of morphofunctional and physical fitness and health.